Low-Tax to GDP Ratio: Causes and Recommendations - Azhar Rashid Khan (Journal of Public Policy Practitioners, 2023)
Tax to GDP reflects the Governments revenue collection through control over all the gross productivity of the nation. The present study highlights the causes of lack of resources for economic development of the country. It further suggests evidence-based policy for Pakistan to make it an industrialized and developed economy by 2025. Secondary data were used to conduct this research. The research found that lack of Political will, the rule of few through exclusion, biased and nepotism in legal & institutional environment like SROs in finance, industry and FBR, are the main causes of low tax to GDP ratio. The study concluded that Pakistan needs to improve its regime of tax collection for one-point agenda of leaving no income untaxed in the country. It should also focus on eliminating exemptions.